Bergamot phytosome improved visceral fat and plasma lipid profiles in overweight and obese class I subject with mild hypercholesterolemia: A randomized placebo controlled trial. (13th November 2020) - Rondanelli, Mariangela; Peroni, Gabriella; Riva, Antonella; Petrangolini, Giovanna; Allegrini, Pietro; Fazia, Teresa; Bernardinelli, Luisa; Naso, Maurizio; Faliva, Milena Anna; Tartara, Alice; Gasparri, Clara; Infantino, Vittoria; et al.
Abstract : Bergamot has been traditionally used for the relief of diseases related to oxidative stress. Our aim was to investigate the effect of bergamot phytosome on visceral adipose tissue (VAT) and on metabolic profile, in overweight and obese subjects with mild hypercholesterolemia. A total of 64 participants were randomized into two groups for 12 weeks: a supplemented group (33 individuals, BMI 27 ± 3 kg/m 2 receiving 500 mg of bergamot phytosome, two daily tablets) and placebo group (31 subjects, BMI 28 ± 3 kg/m 2, two daily tablets). As to the within differences, the parameters of VAT, total and LDL‐cholesterol were significantly decreased in the bergamot phytosome group, but not in the placebo group. As to between‐group differences, a statistically significant interaction between time and group, that is, the change in score over time differs between the two groups was observed 30 days after supplementation for VAT ( p ‐value = .005), total cholesterol ( p ‐value <.0002), and LDL ( p = .004) in respect to placebo. The other parameters (glucose, insulin, Homeostasis Model Assessment, high‐density lipoprotein cholesterol, triglycerides, fat free mass, fat mass) were not significant. In conclusion, this clinical study gives evidence that bergamot phytosome provides beneficial effects, such as decrease of VAT and modulation of metabolic alterations, after just 30 days of supplementation, resulting a very promising protection of cardiovascular health.